Rancang Bangun Aplikasi Booking Kapal untuk Berwisata & Memancing Berbasis Android - Fatmawati; Ahmad Mutedi (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
The development of information technology is increasingly developing, so that makes the human mindset of the desired information needs can be accessed easily, quickly, and accurately. This boat booking is a type of booking that is rarely known by many people and almost everyone only knows about booking hotels, along with the many tourist attractions such as the islands that require tourists to go using the boat to the tourist site, an application is needed to make it easy for tourists to book a ship, from the existing problems for booking and chartering the ship is still done manually by contacting the shipowner directly and for the payment process that is done is still using a manual system that is done after completing using the ship which is feared the charterer can cancel the charter . In this study, the authors used a methodology with data collection techniques namely observation, interviews and literature study while application development uses SDLC (System Development Life Cycle) with a waterfall approach and in this study, the authors used the Fisher-Yates Shuffle algorithm while for modeling using UML (Unified Modeling Language). With the Android-based ship booking application, it can facilitate the tourists in getting information in booking a boat that can be done online.